2005
DOI: 10.1111/j.1440-1819.2005.01365.x
|View full text |Cite
|
Sign up to set email alerts
|

The management of bipolar disorder in primary care: A review of existing and emerging therapies

Abstract: Recent evidence suggests that the prevalence of bipolar disorder is as much as fivefold higher than previously believed, and may amount to nearly 5% of the population, making it almost as common as unipolar major depression. It is, therefore, not unrealistic to assume that primary care or family physicians will frequently encounter bipolar patients in their practice. Such patients may present with a depressive episode, for a variety of medical reasons, for longer-term maintenance after stabilization, and even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 119 publications
0
10
0
1
Order By: Relevance
“…A large number of people with BD are frequently misdiagnosed with unipolar depression in the primary setting. Misdiagnosis may be due in part because they often present during depressive phases of the disorder rather than the manic (21). Piver and colleagues (22) found that up to 30% of the patients who present to primary care clinics as depressed and/or anxious actually have a bipolar spectrum disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of people with BD are frequently misdiagnosed with unipolar depression in the primary setting. Misdiagnosis may be due in part because they often present during depressive phases of the disorder rather than the manic (21). Piver and colleagues (22) found that up to 30% of the patients who present to primary care clinics as depressed and/or anxious actually have a bipolar spectrum disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Piver and colleagues (22) found that up to 30% of the patients who present to primary care clinics as depressed and/or anxious actually have a bipolar spectrum disorder. Consequently, they are often treated with antidepressants alone which may have adverse affect on BD sufferers (21). Thus, the MDQ may still be clinically useful in the primary care setting for both African Americans and those with trauma histories only as a screen for those with possible bipolar disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Stressful events in everyday life in a patient with BD have been associated with a prolonged recovery time from either a depressive or manic episode. Thus, problem solving and establishing routines with regular sleep/wake cycles through cognitive behavioral therapy can not only assist in medication adherence but can also result in decreased hospitalizations (Berk, Dodd, & Berk, 2005). Another useful psychotherapy intervention is interpersonal and social rhythm therapy.…”
Section: Managementmentioning
confidence: 99%
“…In primary care, many bipolar depressed outpatients receive an incorrect diagnosis of unipolar major depression because they spend more time in the depressed phase than in the manic phase (1–4). This is particularly common with past hypomania (bipolar II disorder), where patients usually present for treatment of depression and not for hypomania (which is often a pleasant period of overfunctioning).…”
mentioning
confidence: 99%
“…Conclusion: A well-designed education package on diagnosis and management of bipolar disorder greatly increased the likelihood of physicians correctly assigning a subtype, namely bipolar I or bipolar II disorder, to patients already perceived as having some form of bipolar illness, and to prescribing mood stabilizers instead of antidepressants to these patients. In primary care, many bipolar depressed outpatients receive an incorrect diagnosis of unipolar major depression because they spend more time in the depressed phase than in the manic phase (1)(2)(3)(4). This is particularly common with past hypomania (bipolar II disorder), where patients usually present for treatment of depression and not for hypomania (which is often a pleasant period of overfunctioning).…”
mentioning
confidence: 99%